Architectural accessibility and perception of falls of elderly people in the peridomicile: mixed method - Jéssica de Castro Santos; Cristina Arreguy-Sena; Paulo Ferreira Pinto; Rafael Oliveira Pitta Lopes; Talyta do Carmo Vilela; Marcos Antônio Gomes Brandão (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To describe contents, structure and origin of social representations about falls by elderly people, the peridomiciliary structural conditions that predispose to falls, and to relate the implications of these empirical evidence on the routine of the elderly in the architectural context. Method: Convergent mixed method by triangulation. Qualitative approaches(structural, n=195 and procedural, n=40of the Theory of Social Representations) and quantitative (descriptive sectional, n=183) were used. Elderly people enrolled in primary care were interviewed at home in 2018. Analysis techniques: categorical-thematic, prototypical, statistical, and deductive according to Leininger. Results: Categories of analysis: 1) Peridomicile: fall scenario and 2) Aging and vulnerability: risk of falls in peridomicile. The following environmental characteristics were precursors to falls: uneven floors, holes, unevenness and objects in the pathway. Feelings and behaviors allocated in the possible central core are associated, justifying falls, and determining their causes. Conclusion: There was an association between the peridomiciliary architectural environment and the predictive characteristics of the risk of falls.